Quantitative Analysis Digital Literacy of Secondary and Higher Vocational School Students in the Digital Economy Background - Preliminary Empirical Research Based on 181 Samples from Zhejiang, China - Qiu, Yiting; Li, Lingbo; Wang, Xiaomei (INTI International University, 2024)
Improving digital literacy has become one of China's important strategies in the digital economy era, leading to an important mission of vocational education to cultivate digital talents. A quantitative digital literacy survey was conducted among 181 secondary vocational and higher vocational students in Zhejiang, China. Data analysis showed that the self-score of digital literacy among vocational students was relatively high (3.97/5). Differences in digital literacy between secondary vocational and higher vocational students reached the level of significance, but not between students of different genders or different ages. The four dimensions of digital literacy, digital awareness, computational thinking, digital learning and innovation, and digital social responsibility" have significant correlation pair wisely